Revision and morphological phylogeny of the Neotropical genus Mberu Capellari & Amorim (Diptera: Dolichopodidae), with description of twelve new species - Silva, Paulo Cesar; Capellari, Renato S.; Oliveira, Sarah S. (Zootaxa, 2025)
The genus Mberu Capellari & Amorim of the subfamily Neurigoninae (Dolichopodidae) was previously known only from the type-species. Herein, the genus is revised and now includes thirteen species from Brazil, Argentina and Paraguay, including twelve newly described. All the following species were photographed and a distributional map is also provided: M. altamiro sp. nov., M. amorimi sp. nov., M. bodoquena sp. nov., M. britoi sp. nov., M. ericae sp. nov., M. jawara sp. nov., M. lamasi sp. nov., M. lopesi sp. nov., M. murtiniensis sp. nov., M. pepocatu Capellari & Amorim, 2011, M. periotoi sp. nov., M. soaresi sp. nov. and M. takwajasu sp. nov. An identification key for males of the genus is provided and a morphological phylogenetic analysis of Mberu species is presented, supporting both its monophyly and assignment in the tribe Neurigonini.